Hyperbaric Oxygen Environment Can Enhance Brain Activity and Multitasking Performance - Vadas, Dor; Kalichman, Leonid; Hadanny, Amir; Efrati, Shai (Frontiers in Integrative Neuroscience, 2017)
Abstract Background: The Brain uses 20% of the total oxygen supply consumed by the entire body. Even though, less than 10% of the brain is active at every given time, the brain utilizes almost all the oxygen delivered. In order to perform different tasks or more than one task (multitasking), the oxygen supply is shifted from one brain region to another, via blood perfusion modulation. The aim of the present study was to evaluate whether a hyperbaric oxygen (HBO) environment, with increased oxygen supply to the brain, will enhance the performance of complex and/or multiple activities. Methods: a prospective, double-blind randomized control, crossover trial including 22 healthy volunteers. Participants were asked to perform a cognitive task, a motor task and a simultaneous cognitive-motor task (multitasking). Participants were randomized to perform the tasks in two environments: (a) normobaric air (1ATA 21% oxygen) (b) HBO (2ATA 100% oxygen). Two weeks later participants were crossed to the alternative environment. Blinding of the normobaric environment was achieved in the same chamber with masks on while hyperbaric sensation was simulated by increasing pressure in the first minute and gradually decreasing to normobaric environment prior to tasks performance. Results: Compared to the performance at normobaric conditions, both cognitive and motor single tasks scores were significantly enhanced by the HBO environment (p0.001> for both). Multitasking performance was also significantly enhanced in the HBO environment (p=0.006 for the cognitive part and p=0.02 for the motor part). Conclusions : The improvement in performance of both single and multi-tasking while in an HBO environment supports the hypothesis that oxygen is indeed a rate limiting factor for brain activity. Hyperbaric oxygenation can serve as an enhancing environment for brain performance. Further studies are needed to evaluate the optimal oxygen levels for maximal brain performance.